1997
DOI: 10.1126/science.275.5297.218
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemopreventive Activity of Resveratrol, a Natural Product Derived from Grapes

Abstract: Resveratrol, a phytoalexin found in grapes and other food products, was purified and shown to have cancer chemopreventive activity in assays representing three major stages of carcinogenesis. Resveratrol was found to act as an antioxidant and antimutagen and to induce phase II drug-metabolizing enzymes (anti-initiation activity); it mediated anti-inflammatory effects and inhibited cyclooxygenase and hydroperoxidase functions (antipromotion activity); and it induced human promyelocytic leukemia cell differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

37
2,790
2
38

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,459 publications
(2,916 citation statements)
references
References 23 publications
37
2,790
2
38
Order By: Relevance
“…Similar findings have been reported in human mammary epithelial cells, in which resveratrol inhibited phorbol myristate acetate (PMA)-induced PGE 2 production by blocking transcription and COX enzyme function (32). Studies investigating resveratrol-mediated inhibition of COX in other cell types have demonstrated inhibition of peroxidase function, with no effect on COX enzyme activity (33,34).…”
Section: Discussionsupporting
confidence: 68%
“…Similar findings have been reported in human mammary epithelial cells, in which resveratrol inhibited phorbol myristate acetate (PMA)-induced PGE 2 production by blocking transcription and COX enzyme function (32). Studies investigating resveratrol-mediated inhibition of COX in other cell types have demonstrated inhibition of peroxidase function, with no effect on COX enzyme activity (33,34).…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, they can protect cells from oxidative damage and programmed cell death [7] . Antioxidants prevent carcinogenesis in murine model with anti-apoptotic activity [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Other SERMs like idoxifene (Idox) (Chander et al, 1991;Nuttall et al, 1998), GW 5638 (Willson et al, 1994(Willson et al, , 1997Connor et al, 2001) and EM 800 (Luo et al, 1998;Labrie et al, 1999;Martel et al, 2000) are different from tamoxifen and based on their activity in the rodent uterus are more closely related to raloxifene. Resveratrol (Res) does not formally belong to the SERM family, because it is a phytoestrogen found in the plants (Jang et al, 1997), however Res has similar in vivo characteristics to the SERMs (Mizutani et al, 2000;Bhat and Pezzuto, 2001;Wu et al, 2001). ICI 182,780 (ICI) is a pure anti-oestrogen with anti-oestrogenic activities in almost all tissues, with no changes in serum lipids and on bone density (Wakeling and Bowler, 1987;Wakeling et al, 1991;Lee et al, 2000).…”
mentioning
confidence: 99%